A Rapid Method for Detection of Salmonella in Milk Based on Extraction of mRNA Using Magnetic Capture Probes and RT-qPCR - Bai, Yalong; Cui, Yan; Suo, Yujuan; Shi, Chunlei; Wang, Dapeng; Shi, Xianming (Frontiers in Microbiology, 2019)
Magnetic separation is an efficient method for target enrichment and elimination of inhibitors in the molecular detection systems for foodborne pathogens. In this study, we prepared magnetic capture probes by modifying oligonucleotides complementary to target sequences on the surface of amino-modified silica-coated magnetic nanoparticles and optimized the conditions and parameters of probe synthesis and hybridization. We innovatively put the complexes of magnetic capture probes and target sequences into qPCR without any need for denaturation and purification steps. This strategy can reduce manual steps and save time. We used the magnetic capture probes to separate invA mRNA from Salmonella in artificially contaminated milk samples. The detection sensitivity was 104 CFU/mL, which could be increased to 10 CFU/mL after a 12 h enrichment step. The developed method is robust enough to detect live bacteria in a complex environmental matrix.